Root Traits, Nodulation and Root Distribution in Soil for Five Wild Lentil Species and Lens culinaris (Medik.) Grown under Well-Watered Conditions - Gorim, Linda Y.; Vandenberg, Albert (Frontiers in Plant Science, 2017)
The efficient use of resources such as water and nutrients by plants is increasingly important as the world population food demand continues to grow. With the increased production of lentil in the temperate zones of North America, improvement in yield needs to be maintained. The use of wild lentil genotypes as sources of genetic diversity for introgression into cultivated lentil is an important breeding strategy, but little is known about their root systems. We evaluated the root systems of five wild lentil species and Lens culinaris under fully watered conditions. Plants were grown in 60 cm tubes containing equal volumes of soil collected from the reconstructed A, B, and C horizons. Significant differences were observed for root traits and fine root distribution between and within species and the proportion of root biomass partitioned into each soil layer was unique for each genotype. We also observed variability in nodule number and nodule shape within and between genotypes. Some genotypes more efficiently used water for either biomass or seed production. The allocation of resources to seed production also varied between genotypes. These observations could have impact on the design of future lentil breeding in the context of strategies for managing changes in rainfall amount and distribution for lentil production ecosystems.